Future directions in ultraviolet spectroscopy [electronic resource] : a conference inspired by the accomplishments of the Far Ultraviolet Spectroscopic Explorer Mission : Annapolis, Maryland, 20-22 October 2008 - Future Directions in Ultraviolet Spectroscopy Conference (2008 : Annapolis, Md.); Sonneborn, George (Melville, N.Y. : American Institute of Physics, 2009)
Includes bibliographical references and index